2017
DOI: 10.1088/1361-6528/aa935e
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and cellular uptake of different sized gold nanoparticles in ovarian cancer cells

Abstract: Nanomedicine has advanced the biomedical field with the availability of multifunctional nanoparticles (NPs) systems that can target a disease site enabling drug delivery and helping to monitor the disease. In this paper, we synthesised the gold nanoparticles (AuNPs) with an average size 18, 40, 60 and 80 nm, and studied the effect of nanoparticles size, concentration and incubation time on ovarian cancer cells namely, OVCAR5, OVCAR8, and SKOV3. The size measured by transmission electron microscopy images was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 55 publications
3
34
0
Order By: Relevance
“…A systematic study on spherical GNP ranging from 14–74 nm revealed that nanoparticles with sizes of around 50 nm showed the highest uptake by HeLa cells . However, other studies found that the size dependency for the cellular uptake is less evident or it follows a different pattern with smaller (18 nm) or larger (80 nm) GNP showing enhanced uptake . The opinion is also divided when it comes to comparing spherical and rod‐shaped GNP.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic study on spherical GNP ranging from 14–74 nm revealed that nanoparticles with sizes of around 50 nm showed the highest uptake by HeLa cells . However, other studies found that the size dependency for the cellular uptake is less evident or it follows a different pattern with smaller (18 nm) or larger (80 nm) GNP showing enhanced uptake . The opinion is also divided when it comes to comparing spherical and rod‐shaped GNP.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, AuNPs were found to be cytotoxic to ovarian cancer cells in vitro (OVCAR5, OVCAR8, SKOV3). 35 Another study also confirmed that AuNPs reduced the viability of HeLa cells with IC 50 value obtained at 100 µg/mL concentration, while for bone marrow stem cells the IC 50 value was 300 µg/mL. 36 Generation of ROS is a critical event in causing aging or senescence and apoptosis.…”
Section: Discussionmentioning
confidence: 88%
“…Nanoparticles provide unique and desirable physiochemical properties, ideal for CT imaging. A study by Kumar et al suggested that size and cell type influenced the uptake of “as prepared” AuNPs by ovarian cancer cells [53]. Optimisation of the cellular uptake of AuNPs is required for different cell types to achieve enough payload.…”
Section: Discussionmentioning
confidence: 99%